Babylon : Wissenskultur in Orient und Okzident - Marzahn, Joachim; Cancik-Kirschbaum, Eva Christiane; Cancik-Kirschbaum, Eva Christiane; Ess, Margarete van; Marzahn, Joachim (De Gruyter, 2011)
In diesem interdisziplinären Sammelband, der aus einer Tagung anläßlich der Berliner Ausstellung Babylon - Wahrheit und Mythos hervorgeht, diskutieren international renommierte Wissenschaftler aus den Altertumswissenschaften erstmals unter dem Fokus "Wissenskultur": Für die zeitgenössischen Kulturen der Alten Welt galt Babylon als Inbegriff von Gelehrsamkeit, in den Transformationsprozessen der Spät- und Nachantike hingegen wurde es in dem Maße, wie diese Wissenskultur nach dem Untergang der altorientalischen Reiche in Vergessenheit geriet, zum Sinnbild für Okkultismus, Magie und esoterisches Wissen. Als erstes gemeinsames Pilotprojekt von Topoi und dem Verlag De Gruyter für die zeitgleiche Publikation in Print und Open Access wird dieser Band bei Erscheinen über die Website www.reference-global.de auch als eBook "open access" verfügbar sein.
In this collection of interdisciplinary papers, for the first time well-known scholars of Ancient Near Eastern Studies discuss Babylon from the point of view of the "culture of knowledge". The volume is the result of a conference that took place on the occasion of the exhibition Babylon - Truth and Myth in Berlin. For the contemporary cultures of the Ancient World, Babylon was the epitome of learned scholarship. Yet in the processes of transformation of Late and post-Antiquity, to the same extent to which this culture of knowledge was forgotten after the collapse of the old oriental empires, Babylon became symbolic for the occult, for magic and esoteric knowledge. As the first joint pilot project by Topoi and the publisher De Gruyter for the simultaneous publication in print and open access, this volume will, on publication, also be available via www.reference-global.de as an eBook "open access".
Frontmatter -- Berlin Studies of the Ancient World -- Berlin Studies of the Ancient World -- Inhaltsverzeichnis -- Einführung -- "Babylon - Wissenskulturen zwischen Orient und Okzident" - Programm, Referenten und Podiumsgäste -- Babylon - Heute -- The Present Condition of Babylon / Curtis, John -- The Situation of the Babylon Archaeological Site until 2006 / Musa, Maryam U. -- Excavated and Unexcavated Libraries in Babylon / Pedersén, Olof -- Babylon - Hauptstadt -- Babylon: Origins / Lambert, Wilfred G. -- Babylon in der altbabylonischen Zeit: eine Hauptstadt von vielen ... die als einzige übrig blieb / Charpin, Dominique -- Moving around Babylon: On the Aramean and Chaldean Presence in Southern Mesopotamia / Fales, Frederick M. -- L'écriture publique du pouvoir à Babylone sous Nabuchodonosor II / Joannès, Francis -- Babylon - Wissensort -- Reconstructing Babylon: Recycling Mythological Traditions Toward a New Theology / Katz, Dina -- Die Wissenschaft von der Zukunft. Überlegungen zur Bedeutung der Divination im Alten Orient / Maul, Stefan M. -- Die theoretische Grundlage der babylonischen Heilkunde / Geller, Mark J. -- Bemerkungen zu einigen Aspekten babylonischen Rechtsdenkens im Spannungsfeld von Theorie und Praxis / Neumann, Hans -- "Sieben Tafeln aus sieben Städten". Überlegungen zum Prozess der Serialisierung von Texten in Babylonien in der zweiten Hälfte des zweiten Jahrtausends v. Chr. / Heeßel, Nils P. -- The Role of Babylon in Western Peripheral Education / Soldt, Wilfred van -- Science in Action: Networks in Babylonian Astronomy / Ossendrijver, Mathieu -- Babylon - Wirkungsgeschichten -- Chaldäer im Platonismus / Erler, Michael -- The politai and the bīt tāmartu: The Seleucid and Parthian Theatres of the Greek Citizens of Babylon / Potts, Daniel T. -- Ḥarrān - die Stadt des Sin in islamischer Zeit / Strohmaier, Gotthard -- Die altorientalischen Denkmäler in den Museen in Polen. Geschichte und Bestand / Reiche, Andrzej -- Abstracts -- Abkürzungsverzeichnis -- Indices -- Abbildungsnachweise
Bibliographic Level Mode of Issuance: Monograph
English
Also available in print form.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Learning and scholarship -- Iraq -- Babylon (Extinct city) -- History -- Congresses; Science -- Iraq -- Babylon (Extinct city) -- History -- Congresses; East and West -- History -- Congresses; Babylon (Extinct city) -- Intellectual life -- Congresses; Babylon; Science culture